A Transforaminal Endoscopic Surgical Technique for Treating Lumbar Disc Herniation in the Setting of Spina Bifida - Albert E. Telfeian; Adetokunbo Oyelese; Jared Fridley; Rohaid Ali; Deus Cielo; Ziya L. Gokaslan (Case Reports in Neurological Medicine)
Recent literature suggests that adult patients with spina bifida receive surgery for degenerative disc disease at higher rates than the general population. However, sometimes the complex anatomic features of co-occurring spina bifida and lumbar disc herniation can significantly challenge standard surgical techniques. Here, the technical steps are presented for treating a foraminal lumbar 4-5-disc herniation in the setting of a patient with multifaceted degenerative and spina bifida occulta anatomy. Utilized is a minimally invasive approach that does not require general anesthesia or fusion and allows the patient to leave the same day. To the best of our knowledge, this is the first-reported case of endoscopic surgical decompression of a lumbar disc in a patient with spina bifida.